Postoperative Opioid Use and Pain Management Following Otologic and Neurotologic Surgery. (February 2020) - Boyd, Christopher; Shew, Matthew; Penn, Joseph; Muelleman, Thomas; Lin, James; Staecker, Hinrich; Wichova, Helena
Objectives: The topic of prescription opioid overuse remains a growing concern in the United States. Our objective is to provide insight into pain perception and opioid use based on a patient cohort undergoing common otologic and neurotologic surgeries. Study Design: Prospective observational study with patient questionnaire. Setting: Single academic medical center. Subjects and Methods: Adult patients undergoing otologic and neurotologic procedures by two fellowship trained neurotologists between June and November of 2018 were included in this study. During first postoperative follow-up, participants completed a questionnaire assessing perceived postoperative pain and its impact on quality of life, pain management techniques, and extent of prescription opioid use. Results: A total of 47 patients met inclusion and exclusion criteria. The median pain score was 3 out of 10 (Interquartile Range [IQR] = 2-6) with no significant gender differences ( P  = .92). Patients were prescribed a median of 15.0 (IQR = 10.0-15.0) tablets of opioid pain medication postoperatively, but only used a median of 4.0 (IQR = 1.0-11.5) tablets at the time of first follow-up. Measured quality of life areas included sleep, physical activity, work, and mood. Sleep was most commonly affected, with 69.4% of patients noting disturbances. Conclusions: This study suggests that practitioners may over-estimate the need for opioid pain medication following otologic and neurotologic surgery. It also demonstrates the need for ongoing patient education regarding opioid risks, alternatives, and measures to prevent diversion.